Kesenjangan antara Regulasi dan Praktik Pelaksanaan Perjanjian Perkawinan di Kabupaten Pati Tahun 2020-2025: Perspektif Maslahah Mursalah - Puspita Dwi Safitri; Lina kushidayati (Jurnal Hukum Lex Generalis, 2026)
This study examines the implementation of prenuptial agreements in Pati Regency from the perspective of maslahah mursalah between 2020 and 2025. The primary issue addressed in this study is the low level of public legal awareness and the lack of official registration, which potentially lead to legal uncertainty and future disputes over marital property. The method used is empirical research with a qualitative approach, utilizing interviews, observations, documentation and secondary legal materials. The results indicate that people couple prenuptial agreements due to mixed marriages, property protection, legal awareness, past experiences and concerns over domestic conflicts. However, socio-cultural and economic factors, coupled with the lack of socialization from the Office of Religious Affairs (KUA), contribute to the low utilization of written agreements. The agreements are made in both written and oral forms, yet their implementation often deviates from the initial terms, particularly regarding the mixing of joint property. These findings reflect the couples' level of compliance with the agreements. This study recommends that the Ministry of Religious Affairs and the KUA of Pati Regency mandate socialization regarding the importance of registering prenuptial agreements during pre-marital counseling (bimbingan perkawinan) to minimize the risk of future legal disputes.